2015
DOI: 10.1021/np501057f
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Limonoid Constituents of Munronia henryi

Abstract: Fourteen new limonoids, munronins A-N (1-14), and eight known limonoids (15-22) were isolated from the whole plants of Munronia henryi. The structures of the new compounds were elucidated by 2D NMR spectroscopy and mass spectrometry, and the structure of 8 was confirmed by single-crystal X-ray diffraction analysis. Compound 1 represents the first limonoid found with a novel 7-oxabicyclo[2.2.1]heptane moiety produced by incorporating C-11 and C-14 via an oxygen atom. All compounds were evaluated for their anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 33 publications
0
25
0
1
Order By: Relevance
“…The 1 H NMR spectrum (Table 1) exhibited a β ‐substituted furan ring group ( δ H 7.32, 7.18, 6.20, each 1H, br s), six tertiary methyl groups ( δ H 0.77, 1.17, 1.59, 1.62, 1.87, 2.14, each 3H, s), a methoxy group ( δ H 3.66, 3H, s), and a terminal double bond group ( δ H 5.06, 5.03, each 1H, s), which strongly suggested that 1 was a peieurianin‐type limonoid. The 13 C NMR (Table 1) and HSQC data (Figure S5.1.3) of 1 were very similar to those of munronoid A ( 23 ), [ 18 ] a rings A, B‐ seco limonoid with the conjugated Δ 8,30 and Δ 14,15 double bonds. The planar structure of 1 was established by detailed 2D NMR analysis (Figure 2A), in which the methoxy group was located at C‐3 ( δ C 170.7) instead of C‐7 ( δ C 175.0) by the HMBC correlations of H 3 ‐1′ ( δ H 3.66) and H‐1 ( δ H 5.62) to C‐3.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…The 1 H NMR spectrum (Table 1) exhibited a β ‐substituted furan ring group ( δ H 7.32, 7.18, 6.20, each 1H, br s), six tertiary methyl groups ( δ H 0.77, 1.17, 1.59, 1.62, 1.87, 2.14, each 3H, s), a methoxy group ( δ H 3.66, 3H, s), and a terminal double bond group ( δ H 5.06, 5.03, each 1H, s), which strongly suggested that 1 was a peieurianin‐type limonoid. The 13 C NMR (Table 1) and HSQC data (Figure S5.1.3) of 1 were very similar to those of munronoid A ( 23 ), [ 18 ] a rings A, B‐ seco limonoid with the conjugated Δ 8,30 and Δ 14,15 double bonds. The planar structure of 1 was established by detailed 2D NMR analysis (Figure 2A), in which the methoxy group was located at C‐3 ( δ C 170.7) instead of C‐7 ( δ C 175.0) by the HMBC correlations of H 3 ‐1′ ( δ H 3.66) and H‐1 ( δ H 5.62) to C‐3.…”
Section: Resultsmentioning
confidence: 56%
“…[ 11 ] At present, there are only a few reports on the research of M. unifoliolata , but a large number of limonoids with significant anti‐inflammatory, antimicrobial, and anti‐TMV biological activities have been isolated from its genus. [ 12‐19 ] In order to understand the main and active ingredients of M. unifoliolata , the systematic extraction and separation of dichloromethane extract, the main anti‐inflammatory active portion of the whole plants (IC 50 = 17.9 ± 4.6 μmol/L), were carried out in our current research. This resulted in isolation of twenty‐two new limonoids ( 1 — 22 ), including rings A, B‐ seco , ring A‐ seco , and ring‐intact types.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…However, those with alkynyls usually show potent bioactivity. This may be critical to the anti-TMV and SAR activation activity of munronin O because munronin O is the most potent one among this series of munronins A-V (Yan et al, 2015). It was suggested that the epoxy group is indispensable to the bioactivity of munronin O as well, which was supported by the observation that munronoid O, an epoxy limonoid among munronoids A-O, showed stronger anti-TMV activity than the positive control ningnanmycin (Ge et al, 2012a;Ge et al, 2012b).…”
Section: Limonoids Activate Plant Sar and Inhibit Tmvmentioning
confidence: 91%
“…Munronins B ( 406 ) and H–L ( 407 - 411 ) showed anti-TMV activities with IC 50 values ranging from 19.6 to 44.4 μg/mL (ningnanmycin, 44.6μg/mL). Munronin A ( 412 ) exhibited cytotoxic effects on HL-60 and SW480 cells with IC 50 values of 0.44 and 0.86 μM, respectively (Yan et al, 2015b ). Seven novel daphnane diterpenoids, stelleralides D–J, were obtained from the roots of Stellera chamaejasme (Baotou, Inner Mongolia, China).…”
Section: Terrestrial Plantsmentioning
confidence: 99%